2010
DOI: 10.2355/isijinternational.50.1632
|View full text |Cite
|
Sign up to set email alerts
|

The effect of FetO Content on MgO Solubilities in Lime-based Slags

Abstract: It was attempted to quantitatively elucidate the effect of Fe t O content on MgO solubilities in lime-based slags using the measured data of MgO solubility in the slags. The magnesia capacities of the lime-based liquid slags were nicely correlated with the optical basicities in case the ideal solution was assumed for the magnesiowustite saturation phase which is actually in equilibrium with the slags. The substitution of MgO for CaO in lime-based slags increased the activity coefficient of Fe t O for the const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The relationship between optical basicity and MgO solubility in various slag systems 1, 4, 18, 24 and the present work is shown in Figure 2. The logarithm of the MgO solubility in molten slag (X MgO in slag ) decreases with increasing optical basicity and subsequently the activity of free oxygen ions($a_{{\rm O}^{2- } } $ ), which correlates well with the results of several previous works 1, 4–6, 8, 9, 14. Therefore, low basic slags will typically allow higher dissolution of MgO based refractory if the slag is not properly designed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The relationship between optical basicity and MgO solubility in various slag systems 1, 4, 18, 24 and the present work is shown in Figure 2. The logarithm of the MgO solubility in molten slag (X MgO in slag ) decreases with increasing optical basicity and subsequently the activity of free oxygen ions($a_{{\rm O}^{2- } } $ ), which correlates well with the results of several previous works 1, 4–6, 8, 9, 14. Therefore, low basic slags will typically allow higher dissolution of MgO based refractory if the slag is not properly designed.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of optical basicity has been adopted to evaluate the sulfide capacity, phosphate capacity, and MgO solubility 6–9 of the steelmaking slag system. However, it is reported that those modified values proposed by Duffy and Ingram,23 based on the Pauling electronegativity, does not accurately depict the basic slag systems and in particular those basic slag systems containing the transition metal oxide, such as MnO or FeO 25.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…11 In magnesiowü stite, FeO coexists with MgO and thus affects a MgO . Thus, iron oxide activity a FeO in the magnesiowü stite layer, which equals a FeO in the slag at equilibrium, needs to be calculated.…”
Section: Thermodynamic Considerationsmentioning
confidence: 99%